PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MODEL SHOW AND TELL MELALUI PEMBELAJARAN DARING DENGAN PLATFORM WHATSAPP VIDEO CALL - Niswatun Ngafifah (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
This study aims to improve the speaking skills of fifth-grade students of SD Negeri 1 Kalijoyo for the academic year 2020/2021 by using the Show and Tell model with the whatsapp video call platform. This research is a Classroom Action Research (CAR) which refers to Kurt Lewin (Arikunto, 2015: 42) which consists of four stages of planning, action, observation, and reflection. The research was carried out in two cycles where each cycle was carried out in four meetings. The research subjects were 16 fifth-grade students of SD Negeri 1 Kalijoyo. The techniques accumulation of data is observation, interview, document analyzing, and test. The analysis of data use triangulation technique, triangulation sources, and content validation. This TECHNIQUE research is the interactive analysis model of Miles and Huberman (Sugiyono, 2015: 337) The results of the research data in the first cycle showed that the classical completeness in the pronunciation aspect was 56.20%, the vocabulary aspect was 62.50%, the fluency aspect was 50%, and the accuracy aspect of the story content was 56.20%. Pronunciation is 93.75%, vocabulary aspect is 81.25%, fluency aspect is 87.50%, and story content accuracy is 93.75%. These data indicate that the application of the model Show and Tell with the whatsapp video call platform can improve students' speaking skills.